Sixty years of Swedish computational lexicography - Dannélls, Dana (Digital Linguistics, 2025)
This book offers an in-depth description of how traditional Swedish lexicographical research and cutting-edge language technology are synergetically combined in an e-infrastructure for computational lexicography, improving both natural language processing systems and dictionary compilation.